2011
DOI: 10.1186/1752-1947-5-196
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of the liver: a case report and review of the literature

Abstract: IntroductionInflammatory pseudotumor of the liver represents a fairly uncommon pathology. Although it is a benign tumor, the correct diagnosis can be missed.Case presentationWe report the case of a 55-year-old Caucasian man, who presented with a one-month history of abdominal pain and weight loss. He was diagnosed with a primary liver tumor by computed tomography and magnetic resonance imaging. Alpha-fetoprotein levels ranged within normal limits. A right posterior sectorectomy was performed. Histopathology re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Many mechanisms and hypothesized etiologic factors like infections, trauma, autoimmunity reactions, radiotherapy, and local reaction to changes in the walls of bile ducts are suggested [1][2][3][4][5][6][7]10,13,[18][19][20][21][22][23][24][25][26]. Some microorganisms that access the portal vein including Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Gram-positive cocci and Actinomyces were regarded as causative agents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many mechanisms and hypothesized etiologic factors like infections, trauma, autoimmunity reactions, radiotherapy, and local reaction to changes in the walls of bile ducts are suggested [1][2][3][4][5][6][7]10,13,[18][19][20][21][22][23][24][25][26]. Some microorganisms that access the portal vein including Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Gram-positive cocci and Actinomyces were regarded as causative agents.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections (Epstein-Barr virus [20], hepatitis B and C virus) [10,27] and parasitic infestations (Schistosoma mansoni) may play role in the pathogenesis [18]. Some authors suggested that disturbance of biliary drainage, e.g., due to biliary stones [1,7], recurrent pyogenic cholangitis [4,26] or sclerosing cholangitis is also important [25]. The tumor was also noted in HIV infected persons [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations